Local Food Optimization through Mustard Nugget Processing Innovation Based on Economic Empowerment of Ledokombo Village Community - Amiluddin, Afif; Luqman, Moh; Latifah, Betama Nur; Badriyah, Firdatul; Najilah, Lailatul; Ildayani; Sholehah, Nurfikri Yatus; Wati, Widya Anggraini Eka; Zakia, Nabila Hainun; Hudzaifah; Firmansyah, Wildan Rizqy; Nuraini, Rofifah; Maghfiroh, Siti; Riyani, Vella Putri; Octabryan, Agista Ezha (Indonesian Journal of Community Services Cel, 2024)
Ledokombo Village is situated in a highland area, and most of its residents are farmers. One of the primary commodities cultivated is mustard greens (sawi). However, simultaneous harvesting often leads to oversupply, causing the price of mustard greens to drop significantly. To address this issue, there is a need for solutions to enhance the selling price of mustard greens through processing into other products. In response to this potential, students from the Collaborative KKN Posko 195 initiated a training program for making Frozen Food Sawi Nuggets for the community, mainly targeting the mothers who are cadres of the posyandu (integrated health service post) in Ledokombo Village. This activity was conducted from August 10 to August 15, 2024, at the KKN Posko 195, with the following objectives: to increase the absorption of mustard greens, to provide the community with an understanding of processed mustard green products, and to enhance motivation in creative economics. The training covered various stages, from ingredient preparation to processing, concluding with a socialization session held at the village hall. Participants showed high enthusiasm throughout the training, and the outcome of this activity was an increased understanding of processed mustard greens as Frozen Food Nuggets. This initiative improved the absorption of mustard greens and encouraged the consumption of processed vegetable products. The positive impacts included the enhancement of micro, small, and medium enterprises (MSMEs), a reduction in stunting, and the strengthening of food security in Ledokombo Village.